2011
DOI: 10.1002/ange.201101672
|View full text |Cite
|
Sign up to set email alerts
|

Halogenbrücken‐induzierte Aktivierung einer Kohlenstoff‐ Heteroatom‐Bindung

Abstract: Professor Robert Weiss zum 70. Geburtstag gewidmetHalogenbrücken sind attraktive nichtkovalente Wechselwirkungen zwischen terminalen Halogenatomen in Verbindungen des allgemeinen Typs R-X (X = Cl, Br, I) und LewisBasen (LBs). [1][2][3] Voraussetzung für die Bildung einer starken Halogenbrücke ist ein möglichst elektronegatives Fragment R, beispielsweise in Form polyfluorierter Alkyl-oder Phenylreste (Schema 1). [1,2] Dadurch wird einerseits eine Region positiven elektrostatischen Potentials an der von R abgewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…Preliminary calorimetric measurements gave ab inding constant of approximately 10 6 m À1 for compound 1a with tetrabutylammonium (TBA) bromide in acetonitrile,which is higher (by afactor of 2) than that of our previously employed bidentate XB donor 5a (Figure 4) under identical conditions. [20] Consequently,w ed ecided to use am ore challenging variant of our earlier halide abstraction benchmark reaction (the solvolysis of benzhydryl bromide) [21] and instead investigated the reaction of benzhydryl chloride 6 to acetamide 7 in wet acetonitrile ( Figure 5).…”
Section: Iodine(iii) Derivatives As Halogen Bonding Organocatalystsmentioning
confidence: 99%
“…Preliminary calorimetric measurements gave ab inding constant of approximately 10 6 m À1 for compound 1a with tetrabutylammonium (TBA) bromide in acetonitrile,which is higher (by afactor of 2) than that of our previously employed bidentate XB donor 5a (Figure 4) under identical conditions. [20] Consequently,w ed ecided to use am ore challenging variant of our earlier halide abstraction benchmark reaction (the solvolysis of benzhydryl bromide) [21] and instead investigated the reaction of benzhydryl chloride 6 to acetamide 7 in wet acetonitrile ( Figure 5).…”
Section: Iodine(iii) Derivatives As Halogen Bonding Organocatalystsmentioning
confidence: 99%
“…Astronger Brønsted acid resulted in the production of 3a,albeit in 26 %yield (entry 7), indicating that the acidity of the catalyst affects production of 3a.Indeed, as previously reported, with 10 mol %o ft rimethylsilyl trifluoromethanesulfonate (TMSOTf) [8] as ac onventional Lewis acid, the donor 1 was immediately consumed, and 3a was obtained in 25 %y ield (entry 8), along with several inseparable byproducts.Asthe results were not satisfactory,wenext investigated several XB donors as cooperative catalysts (entries 9-12). We found that combination of thiourea 5 with 2-iodobenzimidazolium-type XB donors 7b [14] afforded 4a as amajor product in 66 %y ield (entry 11). An ewly designed XB donor with extended aromatic rings 7c similarly afforded 4a as the major product (entry 12).…”
mentioning
confidence: 98%
“…[12c] Although thiourea have been recently employed for glycosylation [11] and acetalization [13] of alcohols, its acidity was insufficient to activate trichloroacetimidate. [11a,b] We envisioned that asoft and mild Lewis acid, such as 2-iodoazolium salt [14] (R 2 ¼ 6 H) as halogen bond (XB) donor, [15][16][17] used as ac o-catalyst would interact with the soft Lewis basic moiety of thiourea [18] to increase the HB-donating ability of thiourea, [19] so that the LG could be activated [20] with wide functional group tolerance.The produced N-acylorthoamides [21] would serve as intermediates for thermodynamically favored b-N-glycosides [10] (Scheme 1a,p ath d, Nu = amide), and offer au nique traceless N-glycofunctionalization of amide,i mpacting on prodrug synthesis.I nf act, during the course of our investigation on the rearrangement of Nacylorthoamide to N-glycoside (path d), we have developed an ew type of Brønsted-acid-salt catalyst, comprised of Brønsted acid and 2-halogenated azole,w hich was found to be an efficient catalyst for the direct N-glycosylation of various amides using the same glycosyl trichloroacetimidates (path band/or paths aa nd d).…”
mentioning
confidence: 99%
“…The rarity of functional halogen bonds [5][6][7][8][9][10] compared to the frequency of hydrogen bonds is reminiscent of the situation with anion-p interactions [11] compared to the ubiquitous cation-p interactions. Increasing in strength with halogen atom polarizability, halogen bonds are most efficient with iodine substituents.…”
mentioning
confidence: 99%
“…[7] Halogen bonds have been studied extensively in solid-state crystal engineering. [5] Whereas pioneering examples for rational drug design [8] and anion binding with halogen bonds in solution exist, [9] their application to catalysis [10] and particularly to transport is essentially unexplored.…”
mentioning
confidence: 99%